Pengaruh Manajemen Hybrid Learning dan Fasilitas Belajar Terhadap Kepuasan Mahasiswa - Sri Utaminingsih; Gunawan Setiadi; Suad Suad; Erik Aditia Ismaya (LP. Ma'arif Janggan Magetan, 2024)
The urgency of this research is the need to test the effect of postgraduate elementary education postgraduate student satisfaction analysis on hybrid learning management and learning facilities. The aim of this research is to determine (1) the influence of hybrid learning management on student satisfaction, (2) the influence of learning facilities on student satisfaction, and (3) the influence of hybrid learning management and learning facilities on student satisfaction. This research is a type of ex post facto quantitative research, methodologically it is experimental research which also tests hypotheses but does not carry out treatment. Research procedures include (1) potential and problems, (2) problem formulation, (3) theoretical basis, (4) hypothesis formulation, (5) data collection, (6) instrument testing, (7) data analysis, (8) conclusions. The research population was 300 students from the Postgraduate Basic Education Study Program (S2) with a sample of 50. The research results concluded that hybrid learning management had an effect on student satisfaction (0.000< 0.05), learning facilities also had an effect on student satisfaction (0.001< 0, 05), hybrid learning management and facilities simultaneously influence student satisfaction. The results of the multiple determination coefficient test show a value of 0.823, which means that the hybrid learning management variables and student learning facilities have an influence of 83% on student satisfaction. In the future, it is hoped that there will be an increase in the quality of infrastructure for managing hybrid learning so that services to students can be optimal.